A rare presentation of transverse testicular ectopia and role of laparoscopy - Rajat Piplani (African Journal of Paediatric Surgery, 2023)
Transverse testicular ectopia (TTE) is an uncommon congenital anomaly, in which both the gonads migrate towards the same hemi-scrotum. We report a rare case of TTE discovered coincidentally during surgery in a 1-year-old boy who presented with bilateral undescended testis and right inguinoscrotal swelling. The use of laparoscopy during evaluation for impalpable testis can aid in the diagnosis of TTE, before inguinal exploration. Findings such as the vascular supply and vas deferens of the crossed testis and the identification of Müllerian structures can be confirmed by laparoscopy. Diagnostic laparoscopy was suggestive of both the testes entering in the right-sided open deep inguinal ring, while left-sided deep inguinal ring was found to be closed. There was no evidence of persistent Müllerian structures. On exploration, both testes were present in the right inguinal region. A bilateral trans-septal orchidopexy along with right herniotomy was performed.